Pengaruh Primatani Terhadap Peningkatan Pendapatan Petani Perkebunan di Kecamatan Busungbiu - Arya, NN.; Susrusa, K. Budi; Tenaya, M. Narka (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol. 2 - No. 1 - Mei 2014)
In 2006 up to 2009, Assessment Institue for Agriculture Technology (AIAT)  of Bali,  conducted Primatani assessment in Busungbiu district.  There are several technologies introduced in the study, namely: (1) improvement of cultivation technology of coffee, cocoa, and goats, (2) processing of coffee and cocoa  waste into animal feed, (3) processing of goat manure into organic fertilizer, and  (4 ) processing of integration farming products. In this regard, the research aims to analyze the influence of Primatani to: (1)  farmers income, (2) the extention of farmers' income, (3) contribution of the integration farming income to totally farm household income, (4) employment; ( 5) farmers' income distribution, and (6) the factors that influence farming integration income. The research was conducted in the Sepang and Pucaksari  villages in July to September 2013. Respondents are farmers who implemented farming integration of Robusta coffee plants and goats. They are determined by disproportional random sampling. Respondents were divided into two groups, namely: the  Primatani cooperators  and not Primatani cooperators group. Number of samples are determined by Slovin theory. The data is collected by surveys.   The data was analyzed by independent samples t-test, Lorenz curve, Gini coefficient, and Structural Quation Modeling of Partial Least Square method. The result of analysis showed, (1) the integration farming income in the Primatani cooperators group higher than not Primatani cooperators group; (2) sources of income in the Primatani cooperators group more than not  Primatani cooperators group; (3) contribution of  integration farming income to total income of household  farmers in both sample groups are relatively equal, (4) sum of employ in the Primatani cooperators group higher than not  Primatani cooperators group; (5) equitable distribution of income, and (6) factor of coffee plantation and goats farming influence on integration farming income.
Keywords: primatani, influence, farming integration,coffee plantation,goats, income